Challenges of the leftist current in Brazil during the era of President (DaSilva) - makttoof, Karrar ali (The International and Political Journal, 2023)
There have been sharp fluctuations in the political regimes that Latin America has experienced in recent years. And the developments in several Latin American countries over the past years have revealed the dominance of leftist parties on the political scene. This dominance began to recede after the right-wing parties advanced in large countries such as Brazil, Argentina, Peru, Chile and Paraguay. These developments came as a result of the decline of the democratic approach of the left-wing parties, or as a result of the prosecutions of corruption scandals, as happened in Brazil during the era of President (De Silva) 2003-2011, who failed to face the prosecutions, which affected the bright image of the Latin left. De Silva was not the first leftist to win the rule of their country in South American countries. He was preceded - during the last two years - by the presidents of Bolivia, Peru, Chile, Mexico, Honduras, and Colombia, whose rule (Gustavo Petro) won as its first left-wing president. This was not the only round won by the symbols of the left by ruling the countries of the southern continent, but they also won in a previous round in the first decade of this century, such as Hugo Chavez in Venezuela, Nestor Kirchner in Argentina, Michelle Bachelet in Chile, Jose Mojica in Uruguay, and Evo Morales. in Bolivia, and Rafael Correa in Ecuador.